The Effect of Transformational Leadership and Division of Labor on Performance mediated by Work Motivation, on Employees of the Aru Regency Capital Investment and One-Stop Integrated Services (PTSP) Agency. - Liesal, Benony; Lewaherilla, Novalien.C.; Risambessy, Agusthina (SEAN Institute, 2024)
The purpose of this study is to Influence of Transformational Leadership and Division of Work on Performance mediated by Work Motivation, on Employees of the Capital Investment and One-Stop Integrated Service Agency (PTSP) of Aru Regency. This study is a descriptive quantitative study. The population in this study were 30 respondents of the Capital Investment and One-Stop Integrated Service Agency (PTSP) of Aru Regency. Using a questionnaire. Sampling using non-probability sampling techniques with purposive sampling methods. The data analysis method used is SEM PLS 3.0 to test the formative and reflective models between indicators. Based on the results of the data test that has been carried out, it shows that the transformational leadership variable (X1) has a positive and significant effect on performance (Y), and the division of work variable (X2) as a mediating variable and work motivation variable (Z). Likewise, it has a positive and significant effect on performance (Y) as a mediating variable and work motivation variable (Z). The results of the study also show that transformational leadership has a very high influence on employee performance, the division of work affects performance, and work motivation. This shows that transformational leadership is still dominated by work motivation or references from other people who have a performance commitment.